The chennai glaucoma drops study - MURALI ARIGA,; RAJALAKSHMI.M,; N.PRATHEEBA DEVI,; M.NIVEAN,; M.RAMYAA, (International Journal of Pharma and Bio Sciences, 2017)
Glaucoma is a chronic, progressive and bilateral disease needing long term medications. Increased prevalence of glaucoma, unrestricted access to topical glaucoma medications over the counter, varying prices across the widely available brands are some of the factors that gave significance for taking up our study. Pharmaco-economic analysis of topical glaucoma medications used in Chennai was done. In this study various parameters of the available topical anti-glaucoma medications such as, beta blockers, prostaglandins (PGs), adrenergic agonists, carbonic anhydrase inhibitors (CAI), cholinergic and combination drugs were assessed. It was found that beta blockers were the most inexpensive. Preservative commonly used was Benzalkonium Chloride 0.01%. Sterility of all glaucoma medications were found to be safe. pH of the drops were assessed . The ideal pH of topical medications should be 7 to 7.3, close to the pH of the tear film . Drop size of PGs are ideal for topical medication. Ideal drop size is important to reduce wastage, so that glaucoma medications are not an economic burden to patients. This study could help us as Ophthalmologists to bridge the gap between need, demand and cost.